Analisis Warna pada Pembentukan Suasana Ruang di Kedai Kopi Semi Purworejo - Prastomo, Agustinus Dicky (Universitas Komputer Indonesia, 2023)
The space atmosphere of a coffee shop today, shaped by the natural monochrome colors, has a negative impact on the perceptions of young target consumers. This negative impact emerged during a focus group discussion (FGD) at Kopi Semi coffee shop, Katerban village, Donorejo, Purworejo Regency, Central Java. Apart from FGDs, data collection was also carried out through interviews, questionnaires, physical observations and social media as well as various coffee communities and related agencies under distric government and regional development planning agency. Kopi Semi coffee shop uses the concept of natural dark brown and black coffee colors. This color identification appears in the identity of the logo, furniture, as well as the spatial environment which is then simulated through the visual design. This color is visually perceived as dull, old-fashioned and old by young consumers aged 25-35 years who are targeted as an extension. So that currently loyal consumers are more than 40 years old. It seems that color plays an important role in forming the space atmosphere in the Kopi Semi coffee shop. This research shows that changes to the color concept need to be made. Positive perceptions of color changes in the future, are expected to increase the attractiveness of the space atmosphere in the Kopi Semi coffee shop.